Oral diuretic activity of hot water infusion of Sri Lanka black tea (CameUia sinensis L.) in rats - Abeywickrama, K.R.W.; Ratnasooriya, W.D.; Amarakoon, A.M.T. (My University, 2010)
Black tea [Camellia sinensis (L.) 0 . Kuntze (family: Theaceae)! has been used by Sri Lankan iraditionai practitioners to promote diuresis. However, the type and grade of tea is not specified. Materials and Methods: This study investigates the diuretic activity of black tea infusion (BT!) in rats using Broken Orange Pekoe Fanmngs (BOPF) grad*? major agroclimatic elevations: high-, mjd-, and low-grown. Different concentfations of BTl. furosemide ipositive contro!). and water (vehicle) were orally administered to starved (18 b) male rats (n = 9/group), then hydrated- Acute and chronic (28 days) diuretic activities were assessed by measurinf cumulative urine output at hourly intervals for 6 h. Electrolyte levels (Na", K", C a ' * , H*, C I " , HCO3"), pH, osmolarity of urine, and glomerular filtration rate (GFRi of treated rats were determined. Results: Administration of 8TI induced a significant (P < 0 05) and dose-dependent diuretic activity, which varied with the t ea produced in different agroclimatic elevations. Diuretic activity had 3 lapid onset (1" h;, peaV.ed 2"^ h and maintained up to 4"^ h (except the l ow dose). Furthermore, there was a dose-dependent increase in micturition frequency, which peaked at 2"' h. A close association between the caffeine content of tea and diuretic activity was evident. BTI-induced diuresis was accompanied w i t h an increased urine f^a" level and GFR, The diuretic activity o' was mediated via multiple mechanisms: inhibition of both aldosterone secretion {with increased Na'/K ' ratiQi and carbonrt anhydrase [ w i th decreased CI"'(Na* + K*) ratio] and via thiazide type of diuretic action (evaluated w i th increased ratio). Conclusion; The Sri Lankan BOPF grade black tea possesses mild oral diuretic activity whose efficacy differs the agroclimatic elevation of production. Furthermore, it supports the traditional claim that trie black tea acts as a (Jiiiietic